Implementasi Pembelajaran PJOK di Masa Kebiasaan Baru SD Negeri Se-Kecamatan Wonosari Tahun Ajaran 2021/2022 - Hanafi, Galih Ivan; Farida, Lulu April (Indonesian Journal for Physical Education and Sport, 2023)
This research was conducted to find out how PJOK learning was implemented during the new normal period during the Covid 19 Pandemic in public elementary schools in the Wonosari sub-district for the 2021/2022 Academic Year. This type of research includes a type of quantitative descriptive research using survey methods. The technique used in this study was a total sampling technique with a total of 34 physical education teachers in public elementary schools in the Wonosari District. The results of this study included that all teachers made syllabus and prepared lesson plans before the teaching and learning took place and formulated achievement indicators based on KI & KD. The teachers always explain the scope of the material and the teachers use learning models that can involve students actively, and the teachers evaluate the three aspects consisting of attitudes, knowledge and skills. The conclusion of this study is that PJOK learning planning in the New Normal Period has been carried out very well, then for the Implementation of PJOK learning in the New Habit Period it has been carried out well, as well as for the Evaluation of PJOK learning in the New Habit Period it has been carried out very well.